2012
DOI: 10.1161/circheartfailure.111.962704
|View full text |Cite
|
Sign up to set email alerts
|

Septal Deformation Patterns Delineate Mechanical Dyssynchrony and Regional Differences in Contractility

Abstract: Background-Response to cardiac resynchronization therapy depends both on dyssynchrony and (regional) contractility.We hypothesized that septal deformation can be used to infer integrated information on dyssynchrony and regional contractility, and thereby predict cardiac resynchronization therapy response. Methods and Results-In 132 cardiac resynchronization therapy candidates with left bundle branch block (LBBB)-like electrocardiogram morphology (left ventricular ejection fraction 19Ϯ6%; QRS width 170Ϯ23 ms), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
123
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(138 citation statements)
references
References 43 publications
12
123
0
1
Order By: Relevance
“…Using the CircAdapt model containing wall segments representing the RV free wall, septum and LV free wall, they were able to demonstrate how double-, early-and late-peak septal strain patterns could originate from different combinations of a true electrical substrate of mechanical dyssynchrony whether or not in combination with regional differences in myocardial contractility (see Figure 5). 35 A recent clinical study supported these findings and showed that double-and early-peak septal strain patterns are highly predictive for CRT response. 43 In another CircAdapt study, during gradual pre-excitation of the septum compared with the LV free wall, the time to peak shortening in the septum shortened in two major steps, providing a poor quantitative reflection of true dyssynchrony.…”
Section: Left: Activation Times Calculated By Solving the Eikonal-difmentioning
confidence: 83%
See 1 more Smart Citation
“…Using the CircAdapt model containing wall segments representing the RV free wall, septum and LV free wall, they were able to demonstrate how double-, early-and late-peak septal strain patterns could originate from different combinations of a true electrical substrate of mechanical dyssynchrony whether or not in combination with regional differences in myocardial contractility (see Figure 5). 35 A recent clinical study supported these findings and showed that double-and early-peak septal strain patterns are highly predictive for CRT response. 43 In another CircAdapt study, during gradual pre-excitation of the septum compared with the LV free wall, the time to peak shortening in the septum shortened in two major steps, providing a poor quantitative reflection of true dyssynchrony.…”
Section: Left: Activation Times Calculated By Solving the Eikonal-difmentioning
confidence: 83%
“…35,36 In early-activated regions, a rapid early systolic fibre shortening was found, followed by strongly reduced late systolic shortening. Later-activated regions were characterised by early systolic lengthening followed by pronounced systolic shortening.…”
Section: Some Achievements Of Mechanical Modelsmentioning
confidence: 98%
“…10,12,13 Deformation events were temporally aligned through the ECG-traces, using the onset of the QRS complex as zero strain reference. Global longitudinal strain was used for further analyses.…”
Section: Deformation Analysismentioning
confidence: 99%
“…It enables realistic beat-to-beat simulation of cardiovascular mechanics and hemodynamics under a wide variety of (patho-)physiological circumstances, including ventricular mechanical dyssynchrony. 13,[18][19][20] Three thick-walled segments representing the LV free wall (LVFW), the interventricular septum (SEPT), and the RV free wall are mechanically coupled in a junction and ventricular mechanical interaction is incorporated by the equilibrium of tensile forces in the junction. In each cardiac wall, the myofiber stress-strain relation is determined by a 3-element muscle model describing active and passive cardiac myofiber mechanics.…”
Section: Model Designmentioning
confidence: 99%
“…In patients with LBBB, early systolic septal wall motion, also called septal flash, are often observed. [18][19][20] This slight motion has been noted as an important factor that induces LV dyscoordination and has been reported as a significant predictor of CRT response. Therefore, this novel function could contribute to more accurate assessment of dyssynchrony compared with that provided by currently available systems.…”
mentioning
confidence: 95%